2017
DOI: 10.1371/journal.pone.0175501
|View full text |Cite
|
Sign up to set email alerts
|

The impact of atosiban on pregnancy outcomes in women undergoing in vitro fertilization-embryo transfer: A meta-analysis

Abstract: BackgroundAtosiban is administered to women undergoing in vitro fertilization-embryo transfer (IVF-ET) to improve pregnancy outcomes. However, the results of this treatment were controversial. We conducted this meta-analysis to investigate whether atosiban improves pregnancy outcomes in the women undergoing in vitro fertilization (IVF).MethodsDatabases of PubMed, EMBASE, Web of Science, China BioMedicine, and Google Scholar were systematically searched. Meta-analyses were performed to investigate whether atosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…9, 95% CI: 1.8-4.7). 84 In addition to conflicting results regarding benefit in either a general or specific infertility population, Atosiban has the disadvantage of being an intravenously administered therapeutic.…”
Section: Potential Therapeuticsmentioning
confidence: 99%
“…9, 95% CI: 1.8-4.7). 84 In addition to conflicting results regarding benefit in either a general or specific infertility population, Atosiban has the disadvantage of being an intravenously administered therapeutic.…”
Section: Potential Therapeuticsmentioning
confidence: 99%
“…In recent years, in vitro fertilization‐embryo transfer (IVF‐ET), an accessorial reproduction technology that extracts oocytes from infertile women for fertilization in vitro, has been regarded as one of the most effective therapies for PCOS . Huang et al have explored the effect of body mass index (BMI) on the results of IVF treatment of PCOS patients in China, finding that in comparison with obese women, PCOS women with a BMI of ≥24 kg/m 2 had poorer clinical pregnancy rates.…”
Section: Introductionmentioning
confidence: 99%
“…After a review of the titles and abstracts, 154 studies were identified as potentially eligible for inclusion. After a full review, we excluded 19 systematic reviews or meta-analysis 2,5,22,23,37,[46][47][48][49][50][51][52][53][54][55][56][57][58][59] , 8 case reports [60][61][62][63][64][65][66][67] , 4 letters to the editor [68][69][70][71] and 81 original studies [references and reasons for exclusion are reported in Table 1]. Data on the efficacy of therapies and interventions for RIF were extracted from the remaining 42 articles 8,12,13,18,20,21,24,27,28,31,75, .…”
Section: Resultsmentioning
confidence: 99%